KORELASI NEGATIF ANTARA ASUPAN ENERGI PROTEIN DENGAN NILAI Z SKOR TINGGI BADAN ANAK : STUDI POTONG LINTANG - Sirajuddin Sirajuddin; Agustian Ipa; Adiyatmah Adiyatmah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Introduction: Stunting describes chronic undernutrition during a period of growth and development from the beginning of life. Stunting is a condition where toddlers have a length or height that is less than their age. This situation is determined by looking at the z-score for height for age (TB/U) less than -2 Standard Deviations (SD) based on growth standards according to the World Health Organization (WHO, 2010). Objectives: to determine the percentage of children under five based on stunting, and measure the direction of the correlation between protein energy intake and z score height/ageMethods: This research uses analytic research. This research was conducted to determine the effect of energy and protein intake on the incidence of stunting under five in the stunting locus village, Bone Regency, so that it used a cross sectional study design. Data on energy and protein intake are collected simultaneously with data on the results of measurements of the height of toddlers who are stunted.Results: The results of the study show that the stunting population is 13.3%. Mother's education completed elementary school 51.7%, father's work as a farmer 83.3%, mother's work as a housewife 96.6%. The results of the correlation test show that the direction of the negative correlation between the z-scores of height/age and energy and protein intake is -0.497 and -0.607, respectively. Although both are not significant, respectively p=0.210 and p=0.110.Conclusion: The correlation between the Z score of height/age and energy and protein intake is negative, and not significant